1987
DOI: 10.1537/ase1911.95.137
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of α<sub>2</sub>HS-Glycoprotein Types in Egyptian

Abstract: The polymorphism of *2HS-glycoprotein (*2HS system) was studied in a total of 95 unrelated Egyptian individuals living in Tanta city, Gharbiya province, Nile Delta of Egypt, using isoelectric focusing in thin-layer polyacrylamide gel and immunofixation. Three common phenotypes, *2HS 1, 2-1 and 2 were demonstrated and the estimated allele frequencies were *2HS1= 0.86 and *2HS2=0.14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1988
1988
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…There was also a significant difference between Rome and Cagliari (x2 = 5.53, p< 0.020) The Sardinian sample showed an A2HS*2 frequency (0.168) lower than in most populations examined up to now [2,4,6,[9][10][11][12][13]. It is interesting to note that the only other population with a similar A2HS*2 frequency (0.142) is the Egyptian one [1]. This seems to be in agreement with previously reported results [3,5,7] sug gesting that the influence of populations from Africa and the Middle East may have contributed to the genetic structure of the present Sardinian population.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…There was also a significant difference between Rome and Cagliari (x2 = 5.53, p< 0.020) The Sardinian sample showed an A2HS*2 frequency (0.168) lower than in most populations examined up to now [2,4,6,[9][10][11][12][13]. It is interesting to note that the only other population with a similar A2HS*2 frequency (0.142) is the Egyptian one [1]. This seems to be in agreement with previously reported results [3,5,7] sug gesting that the influence of populations from Africa and the Middle East may have contributed to the genetic structure of the present Sardinian population.…”
Section: Methodsmentioning
confidence: 75%
“…Up to now mostly non-European populations have been examined [1,2,4,9,12,13]. In Europe, French, German and English populations have been studied [6,10,11], The present work reports allele frequencies of A2HS in continental Italy and in Sardinia.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations [2][3][4][5][6][7][8][9][10] have shown that the polymorphism of this serum protein is represented by two common and several rare alleles at a single autosomal gene locus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of genetic polymorphism of hu man serum oçHS-glycoprotein (A2HS) have been undertaken in several popula tions [1][2][3][4][5][6][7][8][9][10][11][12] and a number of rare alleles have been reported [4,10,11,13]. No pop ulation in Polynesia has been studied so far.…”
Section: Introductionmentioning
confidence: 99%